Biological upcycling of conditionally biodegradable plastics: enzymatic depolymerization to microbial valorization and consolidated bioprocessing frameworks - Yunhee Jeong; Sol Min Han; Jieun Wu; KwangYoung Park; Yunjeong Song; Yung-Hun Yang; Kyung-Jin Kim; Jungoh Ahn; Kyungmoon Park; See-Hyoung Park; Si Jae Park; Eun Ju Yun; et al. (Systems Microbiology and Biomanufacturing, 2026)

Robust Relative Space Motion Control of Underwater Vehicles Using Time Delay Estimation - Gun Rae Cho; Hyungjoo Kang; Min-Gyu Kim; Sungho Park; Chulhee Bae; Han-Sol Jin; Seongho Jin; Ji-Hong Li (Journal of Marine Science and Engineering, 2025)
This paper presents a robust trajectory-tracking control framework for underwater vehicles operating in a relative coordinate system. Unlike conventional methods that define trajectories in the world frame, the proposed approach formulates the control problem directly in a moving reference frame, enabling accurate motion control with respect to dynamic and drifting objects affected by environmental disturbances such as ocean currents and waves. This relative-space formulation is particularly advantageous for tasks including diver guidance, floating-object inspection, and docking, where the reference itself is nonstationary. A coordinate transformation is introduced to consistently express the vehicle dynamics in the relative frame. Based on the transformed dynamics, a Time Delay Control (TDC) law is applied to estimate unmodeled dynamics and external disturbances without requiring precise system parameters. Theoretical stability analysis shows that the stability condition of the proposed controller is consistent with that of conventional TDC, allowing similar gain-tuning procedures. Simulation results demonstrate that the proposed controller achieves robust and smooth trajectory tracking even when the reference frame undergoes motion induced by ocean currents.

Evaluating nuclear (18S, ITS, and 28S) and chloroplast (psbB, psbC, rbcL, and tufA) genes of the green algae Monoraphidium (Sphaeropleales, Chlorophyta) for DNA barcoding - Ha-Eun Lee; Taehee Kim; Han-Sol Kim; Ok-Min Lee; Jang-Seu Ki (Algae, 2025)
The genus Monoraphidium is a green microalgae distributed globally in freshwater ecosystems, and it is difficult to classify morphologically. Molecular genetic markers have been used for their taxonomy, although they have not been thoroughly evaluated. Here, we investigated three nuclear rRNA molecules (18S, internal transcribed spacer [ITS] + 5.8S, and 28S) and four chloroplast genes (psbB, psbC, rbcL, and tufA) using 16 Monoraphidium strains consisting of 9 species. Upon comparisons of genetic diversity and marker performance evaluation, we found that ITS was the best marker for Monoraphidium to discriminate each species, followed by tufA. The taxonomic discrimination power of the ITS was supported by the neighbor-joining tree. In addition, a secondary structure of ITS2 combined with compensatory base changes showed the distinct differences among individual species of Monoraphidium. These suggest that ITS may be the best marker for species differentiation of the coccoid green algae Monoraphidium.

Adlercreutzia faecimuris sp. nov., producing propionate and acetate isolated from mouse feces - Min Kuk Suh; Jong- Sik Jin; Hyo Eun Do; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

Phocaeicola acetigenes sp. nov., producing acetic acid and iso-butyric acid, isolated faeces from a healthy human - Hyo Eun Do; Young Bong Ha; Ji-Sun Kim; Min Kuk Suh; Han Sol Kim; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; et al. (Antonie van Leeuwenhoek, 2024)

Jatrophihabitans cynanchi sp. nov., isolated from rhizosphere soil of Cynanchum wilfordii - Min Kuk Suh; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Hyo Eun Do; Yong Kook Shin; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

Full Coverage Path Planning for Torpedo-Type AUVs’ Marine Survey Confined in Convex Polygon Area - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Han-Sol Jin (Journal of Marine Science and Engineering, 2024)
In this paper, we present a full coverage path planning (CPP) algorithm for the marine surveys conducted in the convex polygon shaped search area. The survey is supposed to carry out by torpedo-type AUVs (autonomous underwater vehicles). Due to their nonholonomic mechanical characteristics, these vehicles have nonzero minimum turning radius. For any given polygon shaped search area, it can always be partitioned into one or more convex polygons. With this in mind, this paper proposes a novel search algorithm called CbSPSA (Calculation based Shortest Path Search Algorithm) for full coverage of any given convex polygon shaped search area. By aligning the search inter-tracks alongside the edge with the minimum height, we can guarantee the minimum number of the vehicle’s turns. In addition, the proposed method can guarantee the planned path is strictly located inside the polygon area without overlapped or crossed path lines, and also has the total path length as short as possible. Considering the vehicle’s nonzero minimum turning radius, we also propose a sort of smoothing algorithm which can smooth the waypoint path searched by CbSPSA so that the vehicle can exactly follow it. The smoothed path is also guaranteed to be strictly located inside the polygon. Numerical simulation analyses are also carried out to verify the effectiveness of the proposed schemes.

Gordonibacter faecis sp. nov., producing urolithin C from ellagic acid, isolated from feces of healthy Korean subjects - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Hyo Eun Do; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2024)

Hypoxia-alleviating hemoglobin nanoclusters for sensitizing chemo-photodynamic therapy of cervical cancer - Han Sol Lee; So-Yeol Yoo; Sang Min Lee; Nae-Won Kang; Sang Kyum Kim; Gyu Yong Song; Dae-Duk Kim; Jae-Young Lee (Chemical Engineering Journal, 2023)

Adaptive Formation Control of Multiple Underactuated Autonomous Underwater Vehicles - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Gun Rae Cho; Han-Sol Jin (Journal of Marine Science and Engineering, 2022)
In this paper, we present a 3D formation control scheme for a group of torpedo-type underactuated autonomous underwater vehicles (AUVs). These multiple AUVs combined with an unmanned surface vessel (USV) construct a sort of star-topology acoustic communication network where the USV is at the center point. Due to this kind of topological feature, this paper applies a virtual school concept. This is a geometric graph where each node is taken as a virtual leader for each specific AUV and assigned its own reference trajectory. For each individual vehicle, its formation strategy is simple: just follow the trajectory of its corresponding virtual leader so as for multiple AUVs to compose the given formation. As for the formation subject, this paper mainly focuses on the formation tracking problem rather than the formation producing. For the torpedo-type vehicle considered in this paper, there are only three control inputs (surge force, pitch, and yaw moments) available for its underwater 3D motion and therefore this is a typical underactuated system. For the following vehicle’s trajectory, a sort of potential field method is used for obstacle avoidance, and a neural network-based adaptive scheme is applied to on-line approximate the vehicle’s unknown nonlinear dynamics, and the uncertainty terms including modeling errors, measurement noises, and external disturbances are handled by the properly designed robust scheme. The proposed formation method can guarantee the uniform ultimate boundedness (UUB) of the closed-loop system. Numerical studies are also carried out to verify the effectiveness of the proposed scheme.

Bacteroides humanifaecis sp. nov., isolated from faeces of healthy Korean - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2022)

Marinobacter arenosus sp. nov., a halotolerant bacterium isolated from a tidal flat - Yunjeong Lee; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Arenibacterium arenosum sp. nov., isolated from sea sand - Jiseon Jeong; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

An overview of chondrosarcoma with a focus on nanoscale therapeutics - Dong Hyun Kim; Han Sol Lee; Yong-Hyeon Mun; SeokJin Koh; Joon-Sun Park; Sang Min Lee; Nae-Won Kang; Mee Yeon Lee; Cheong-Weon Cho; Dae-Duk Kim; Jae-Young Lee (Journal of Pharmaceutical Investigation, 2020)

Comamonas flocculans sp. nov., a Floc-Forming Bacterium Isolated from Livestock Wastewater - Dong-Hyun Kim; Kook-Il Han; Hae-Jun Kwon; Mi-Gyeong Kim; Young-Guk Kim; Doo-Ho Choi; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jong-Guk Kim (Current Microbiology, 2020)

Experimental and Numerical Investigation of Self-Burial Mechanism of Pipeline with Spoiler under Steady Flow Conditions - Woo-Dong Lee; Hyo-Jae Jo; Han-Sol Kim; Min-Jun Kang; Kwang-Hyo Jung; Dong-Soo Hur (Journal of Marine Science and Engineering, 2019)
Herein, hydraulic model experiments and numerical simulations were performed to understand the self-burial mechanism of subsea pipelines with spoilers under steady flow conditions. First, scour characteristics and self-burial functions according to the spoiler length-to-pipe diameter ratio (S/D) were investigated through hydraulic experiments. Further, the Navier–Stokes solver was verified. The experimental values of the velocity at the bottom of the pipeline with a spoiler and the pressure on the sand foundation where the pipeline rested were represented with the degree of conformity. Scour characteristics of a sand foundation were investigated from the numerical analysis results of the velocity and vorticity surrounding the pipelines with spoilers. The compilation of results from the hydraulic experiment and numerical analysis showed that the projected area increased when a spoiler was attached to the subsea pipes. This consequently increased the velocity of fluid leaving the top and bottom of the pipe, and high vorticity was formed within and above the sand foundation. This aggravated scouring at the pipe base and increased the top and bottom asymmetry of the dynamic pressure field, which developed a downward force on the pipeline. These two primary effects acting simultaneously under steady flow conditions explained the self-burial of pipelines with a spoiler attachment.

Improvement of cellular uptake of hydrophilic molecule, calcein, formulated by liposome - Su-Min Han; Young-Guk Na; Han-Sol Lee; Gi-Ho Son; Seong-Hoon Jeon; Ki-Hyun Bang; Sung-Jin Kim; Hye-Jin Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2018)

Sphingosine-1-phosphate is involved in inflammatory reactions in patients with Graves’ orbitopathy - Yuri Seo; Min Kyung Chae; Sol Ah Han; Eun Jig Lee; Joon H. Lee; Jin Sook Yoon (Inflammation Research, 2017)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

Evaluating client application status for V-World Open API service - Han-sol Jang; Dong-kyu Kim; Jung-min Kim; In-sung Jang (Spatial Information Research, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Spirosoma radiotolerans sp. nov., a Gamma-Radiation-Resistant Bacterium Isolated from Gamma Ray-Irradiated Soil - Jae-Jin Lee; Sathiyaraj Srinivasan; Sangyong Lim; Minho Joe; Seonghun Im; So Il Bae; Kyoung Ryun Park; Ji-Hee Han; Se-Hee Park; Bo-min Joo; Sol-Ji Park; Myung Kyum Kim (Current Microbiology, 2014)